2003
DOI: 10.1111/1528-3577.402001
|View full text |Cite
|
Sign up to set email alerts
|

Samuel Huntington and the Geopolitics of American Identity: The Function of Foreign Policy in America's Domestic Clash of Civilizations

Abstract: The clash of civilizations thesis's true origins lie partly in problems Samuel Huntington sees brewing in his own country. His thesis is to a considerable extent an externalization of these troubles––an attempt to solve them through international means, while serving U.S. national interests in tandem. As a scholar of American exceptionalism Huntington is––explicitly and openly––concerned about the political unity and cultural homogeneity of his country in the absence of the existential threat of world Communis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Focusing selectively on some aspects of the CoC theory can provide an explanation for why they are a threat, if one does not look too closely at all aspects of the theory. Fourth, it is a convenient theory to cite for those who wish to disagree with multiculturalism and Westerners who seek to identify enemies (Aysha 2003). Finally, if one does not engage in a systematic analysis which considers all aspects of the theory and all relevant conflicts, it is easy to find examples which fit the theory and ignore those which do not.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing selectively on some aspects of the CoC theory can provide an explanation for why they are a threat, if one does not look too closely at all aspects of the theory. Fourth, it is a convenient theory to cite for those who wish to disagree with multiculturalism and Westerners who seek to identify enemies (Aysha 2003). Finally, if one does not engage in a systematic analysis which considers all aspects of the theory and all relevant conflicts, it is easy to find examples which fit the theory and ignore those which do not.…”
Section: Discussionmentioning
confidence: 99%
“…Questions arising in relation to Samuel Huntington's clash of civilizations thesis amount to a reissued call for careful consideration of reasons for conducting crosscultural research on a particular topic and for thinking through the implications of potential biases, ambiguities, and blank spaces (Aysha 2003; Dallmayr 2001; de Soysa and Nordås 2007; Huntington 1993, 1996; Said 2002; and Sen 2008). 22 Many are emphatic that we need to move beyond pointed polemics and debunking messages to develop “alternative ways of thinking about crosscultural exchange” (Chow 2002, 109–10; de Soysa and Nordås 2007; Panikkar 1981, 44–45).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The 11 September 2001 event, terrorist attacks on the US, and events subsequent, appeared to vindicate claims regarding the stubborn persistence of cultural particularisms in the face of universalising trends of globalisation. Some even suggested that Samuel Huntington's much-maligned thesis about the inevitable clash of civilisations, with 'real and basic' differences, had perhaps been prescient (Aysha 2003;Norris and Inglehart 2002).…”
Section: Globalisation and Belongingmentioning
confidence: 99%